Semantics of possessive determiners - Peters, Stanley; Westerståhl, Dag (Proceedings of the Amsterdam Colloquium, 2005)
We give a uniform account of a wide range of possessive determiners, including simple (John’s), quantified (few doctors’), and partitive (each of most students’), focusing on certain (frequently neglected) features of their semantics. One is the mode of quantification over the ‘possessed’ objects: often universal, but other modes are allowed too. Another is what Barker 1995 calls narrowing: we agree that it belongs to the semantics of possessives but note that it appears to lead to certain methodological problems. A third is the role of definiteness for possessives: we compare our account to the ‘definiteness account’ common in the literature, and in particular discuss the definiteness of partitives. Fourth, we study the monotonicity behavior of possessives.